Large-scale variations in ozone and polar stratospheric clouds measured with airborne lidar during formation of the 1987 ozone hole over Antarctica - Kooi, Susan A.; Tuck, Adrian; Poole, Lamont R.; Mccormick, M. Patrick; Browell, Edward V.; Ismail, Syed; Butler, Carolyn F.; Krueger, Arlin J.; Jones, Rod; Szedlmayer, Margaret M. (1988)
A joint field experiment between NASA and NOAA was conducted during August to September 1987 to obtain in situ and remote measurements of key gases and aerosols from aircraft platforms during the formation of the ozone (O3) hole over Antarctica. The ER-2 (advanced U-2) and DC-8 aircraft from the NASA Ames Research Center were used in this field experiment. The NASA Langley Research Center's airborne differential absorption lidar (DIAL) system was operated from the DC-8 to obtain profiles of O3 and polar stratospheric clouds in the lower stratosphere during long-range flights over Antarctica from August 28 to September 29, 1987. The airborne DIAL system was configured to transmit simultaneously four laser wavelengths (301, 311, 622, and 1064 nm) above the DC-8 for DIAL measurements of O3 profiles between 11 to 20 km ASL (geometric altitude above sea level) and multiple wavelength aerosol backscatter measurements between 11 to 24 km ASL. A total of 13 DC-8 flights were made over Antarctica with 2 flights reaching the South Pole. Polar stratospheric clouds (PSC's) were detected in multiple thin layers in the 11 to 21 km ASL altitude range with each layer having a typical thickness of less than 1 km. Two types of PSC's were found based on aerosol backscattering ratios: predominantly water ice clouds (type 2) and clouds with scattering characteristics consistent with binary solid nitric acid/water clouds (type 1). Large-scale cross sections of O3 distributions were obtained. The data provides additional information about a potentially important transport mechanism that may influence the O3 budget inside the vortex. There is also some evidence that strong low pressure systems in the troposphere are associated with regions of lower stratospheric O3. This paper discusses the spatial and temporal variations of O3 inside and outside the polar vortex region during the development of the O3 hole and relates these data to other measurements obtained during this field experiment.